A Noblewoman's Changing Perspective on the World: The Habsburg Patriotism of Rosa Neipperg-Lobkowicz (1832–1905). (14th July 2016) - Godsey, William D.
Abstract : Until not so very long ago, the national conflicts in the last decades of the Habsburg monarchy prompted historians to focus on nationality as the crucial marker of self-understanding among its populations. The high tide of modern nation-states after 1918 made national borders, national mindsets, and national power structures the framework for ever-greater historical interest in the lineages of national genealogy. In recent decades, scholars have questioned the assumption that modern nations were primordial or natural, even as such entities remain a prime object of attention in a world where nation-states and identity politics help define research agendas and nationalism continues to be a potent force. The lines of inquiry have taken a number of directions. First, historians have linked the pervasiveness of nation and national identity to specific historical circumstances. Perhaps most famously, the political scientist Benedict Anderson's insight regarding "imagined communities" pointed up the contingency of modern nations. It was increasingly accepted that they are artificial constructs of relatively recent date and firmly rooted in time and place. The neat boundaries that seemed to define them, as on old ethnographic maps, faded as their elusive, conditional, and shifting contours were recognized.